2021
DOI: 10.3389/feduc.2020.565722
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Resilience Strategies: Voices From Chinese Novice Foreign Language Teachers

Abstract: In recent years, due to the concern of the high rate of burnout and attrition of teachers in their early career years, teacher resilience has become a vital theme in the study of their professional development. However, little has been done in China. This study contextualized teacher resilience development in Chinese universities and interviewed seven resilient novice foreign language (FL) teachers to explore risk factors confronting them in Chinese contexts and resilience strategies they have employed to cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Resilience, defined at the end of the 20th century [30,31], can be considered a strategy put in place to cope with stressful situations [24,[32][33][34]. It is the ability to be able to adapt to adverse situations [15,[35][36][37]. Aspects such as people's positive emotions (happiness, optimism, self-esteem, and assertiveness that the individual possesses) will be fundamental in the face of these problematic situations [38,39].…”
Section: Resiliencementioning
confidence: 99%
See 3 more Smart Citations
“…Resilience, defined at the end of the 20th century [30,31], can be considered a strategy put in place to cope with stressful situations [24,[32][33][34]. It is the ability to be able to adapt to adverse situations [15,[35][36][37]. Aspects such as people's positive emotions (happiness, optimism, self-esteem, and assertiveness that the individual possesses) will be fundamental in the face of these problematic situations [38,39].…”
Section: Resiliencementioning
confidence: 99%
“…It has also been observed that those teachers who possessed stronger thoughts and emotions were able to cope with situations that required firm temperance and thus reduce the effects of stress that could cause them [36]. It is the responsibility of the educational system to develop such strategies and introduce resilience in teacher training plans as it results in better qualified people [15,[42][43][44]]. An example is the SmartInEducation methodology aimed at developing resilience and stress management techniques [45].…”
Section: Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…An overview of previous studies reveals that almost all the research on teacher resilience were conducted in Western contexts ( Fan et al, 2021 ; Wang et al, 2021 ). Few studies focus on the risk factors and resilience measures adopted by foreign language teachers in the Chinese context, which is characterized with examination-oriented education and national reform policy ( Fan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%